2009
DOI: 10.2139/ssrn.1508431
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Newspaper Entry and Exit on Electoral Politics

Abstract: The views expressed herein are those of the author(s) and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 56 publications
2
57
0
Order By: Relevance
“…The introduction of paywalls disproportionately excludes young readers, which undermines policymakers' attempts to create a comprehensive community. Scholars have emphasized that newspaper readership as imperative to the promotion of democracy and civic engagement (Putnam, 2000;Feddersen, 2004;Oberholzer-Gee and Waldfogel, 2009;Gentzkow et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of paywalls disproportionately excludes young readers, which undermines policymakers' attempts to create a comprehensive community. Scholars have emphasized that newspaper readership as imperative to the promotion of democracy and civic engagement (Putnam, 2000;Feddersen, 2004;Oberholzer-Gee and Waldfogel, 2009;Gentzkow et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, studies have shown that the diffusion of news media is associated with positive spillovers on civic awareness and engagement (Mondak, 1995a,b;Lee and Wei, 2008;Oberholzer-Gee and Waldfogel, 2009;Gentzkow et al, 2009). Though the Internet facilitates the spread of information, it is not clear how or whether news organizations should charge for their content and how this might affect consumption of the news.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the higher number of competing media outlets present in the online market for news seems to be associated with a higher degree of ideological polarization with respect to the offline market for news (Sunstein, Moreover, since the higher the opportunity cost of acquiring information, the less extremists citizens will find it optimal to acquire information, as such cost increases the likelihood of media outlets choosing ideological editors decreases. 30 That is, it is possible to reinterpret the above proposition with respect to C. For a given K > 2, there will exist a C * (K) such that for C > C * (K), all media outlets will choose a moderate editor from the population of citizens. Instead, for C < C * (K), media outlets will choose ideological editors.…”
Section: Proposition 4 Suppose That Citizen's Idiosyncratic Preferencmentioning
confidence: 99%
“…The analysis thus suggests that, all other things equal, more moderate editors should be present in the press sector than in the broadcast media sector. At the same time, there should be more extremist citizens watching 30 …”
Section: Proposition 4 Suppose That Citizen's Idiosyncratic Preferencmentioning
confidence: 99%
“…These include, apart from demographic or economic characteristics, the weather Gomez 2010, Gomez et al 2007), general rules of governance (Hinnerich andPettersson Lidbom 2014, Herrera, Morelli andPalfrey 2014), voting systems (Braconnuer, Dormagen andPons 2014), candidates' ethnicity (Washington 2006), and availability of certain information technology (Stromberg 2004, Enikolopov, Petrova and Zhuravskaya 2010, Gentzkow, Shapiro and Sinkinson 2011, Gentzkow 2006and Gavazza, Nardotto and Valletti 2014. Like infections incidence, these factors may impact public policy, through their effect on variables other than voting cost or through their impact on the political affiliation of elected representatives -that is, directly or indirectly.…”
mentioning
confidence: 99%